Kekuatan dan Kelemahan Sistem Pengawasan dan Pengendalian Perbankan Syariah di Indonesia - Alhalimi, Kamila; Andrini, Rozi (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Islamic banking in Indonesia has experienced significant growth over the past two decades, contributing to the national financial system. This study aims to analyze the strengths and weaknesses of the supervisory and control system for Islamic banking in Indonesia. The methodology employed in this research is a qualitative approach with descriptive analysis, including literature studies and interviews with experts in the field of Islamic banking. The results indicate that although the regulatory framework for Islamic banking in Indonesia has developed well, challenges in human resource development, technological infrastructure, and regulatory harmonization persist. Efforts are needed to enhance the competencies of Islamic banking supervisors and integrate technology to address challenges in the current digital era. This research provides recommendations for improving the effectiveness of supervision and control of Islamic banking in Indonesia to contribute more significantly to national economic stability and growth.